Relation between CYP2D6 Genotype, Phenotype and Therapeutic Drug Concentrations among Nortriptyline and Venlafaxine Users in Old Age Psychiatry - Berm, E.; Kok, R.; Hak, E.; Wilffert, B. (Pharmacopsychiatry, 2016)
Objectives: To determine relations between drug concentrations and the cytochrome P450-CYP2D6 genotype or phenotype among elderly patients treated with nortriptyline or venlafaxine.Methods: A post-hoc analysis of a clinical trial was performed. Patients were grouped into phenotypes according to the metabolite/mother compound ratio. Genotypes were assessed by the CYP2D6 *3 and *4 alleles.Results: Data was available from 81 patients (41 nortriptyline, 40 venlafaxine) with a mean age of 72 years. No phenoconversion from poor metabolizers (PM) to extensive metabolizers (EM), or vice versa, was found. However, we did find phenoconversion from PM to intermediate metabolizers (IM), IM to EM, or vice versa in 36% of observations. Among nortriptyline users, patients with a PM or IM genotype had more supra-therapeutic blood levels, although this did not reach statistical significance. In exploratory analyses we found men were more likely (RR: 2.4; 95% CI: 1.14–5.07) to display phenoconversion from an IM genotype to EM phenotype. In addition, compared to non-PMs, PMs were found to have higher risk (RR: 1.56; 95% CI: 1.03–2.37) on non-response, although this was only significant when response was measured on the Hamilton Rating Scale for Depression and not on the Montgomery Åsberg Depression Rating Scale.Conclusion: Patients phenoconversed, but we did not observe phenoconversion from PM to EM or vice versa. Genotype information could be used as a valuable tool, in addition to therapeutic drug monitoring, to prevent supratherapeutic drug levels of nortriptyline or venlafaxine in elderly patients with a PM genotype.
Keywords: depression; genetics; cytochrome P450 (CYP) enzymes; venlafaxine; nortriptyline